Performance assessment of a cylindrospermopsin ELISA with purified compounds and cyanobacterial extracts. Issue 2 (3rd April 2017) - Metcalf, J. S.; Young, F. M.; Codd, G. A.
ABSTRACT: Detecting low amounts of cyanobacterial toxins (cyanotoxins) in water and clinical materials is useful to protect human health and to understand cyanotoxin intoxication events. Commonly-occurring cyanobacterial compounds and extracts of cyanotoxin-producing cyanobacteria were tested by a cylindrospermopsin ELISA, in comparison with HPLC-PDA. Other than the cylindrospermopsin variants, none of the purified cyanobacterial peptides tested showed cross-reactivity in the cylindrospermopsin ELISA up to 100 µg/L, with the exception of nodularin-R. The cylindrospermopsin concentration in cylindrospermopsin-producing cyanobacteria showed good agreement between ELISA and HPLC-PDA. However, extracts of Microcystis, Planktothrix, Nodularia, and Chlorella showed ELISA positives with such non-cylindrospermopsin-producing organisms reporting concentrations greater than 1 µg/L. When cylindrospermopsins were present, the cylindrospermopsin ELISA yielded good quantification, but false positive results from non-cylindrospermopsin-containing cyanobacteria and microalgae could not be discounted.